DAMPAK GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Pernanda, Dody; Sutrisno, Jhon; Yansyah, Rusli (Fakultas Ekonomi Universitas Djuanda, 2025)
This study aims to analyze the positive and significant effects, both partially and simultaneously, of leadership style and motivation on employee performance at PT. Victoria Care Indonesia in West Jakarta. The focus of the study is to determine the extent to which these two independent variables can improve employee effectiveness and productivity. This study uses a quantitative approach with saturated sampling technique, where the entire population of 70 employees is used as the research sample. Data were collected through observation and structured questionnaires measured using a Likert scale. Data analysis was performed using classical assumption tests, simple and multiple linear regression analysis, correlation coefficient tests, determination coefficients, and hypothesis testing using t-tests and F-tests. The results showed that leadership style had a positive effect on employee performance. Motivation also has a positive effect on employee performance. Simultaneously, leadership style and motivation have a significant effect on employee performance, with the equation showing a positive and significant effect between the two independent variables on employee performance. These findings confirm that improving effective leadership style and high work motivation can encourage improved employee performance in the corporate environment.